MODEL KEMITRAAN PADA UMKM JAMU TRADISIONAL MADURA MELALUI PENDEKATAN ANALYTICAL HIERARCHY PROCESS - Yanuba Cahya Ramadhanti; Resti Prastika Destiarni; Dewi Muti’ah (Universitas Galuh, 2022)
Pamekasan Regency is one of the areas on the island of Madura which has potential in the field of production and development of traditional herbal medicine. However, until now, the existence of traditional herbal medicine SMEs in Pamekasan has been carried out individually and developed according to natural selection and there has not been a partnership that accommodates it. The purpose of this study is to analyze the appropriate partnership model for traditional Madura herbal medicine SMEs in Pamekasan Regency. The method used in this research is the Analytical Hierarchy Process (AHP). The results showed that the traditional herbal medicine SMEs in Pamekasan Regency were entirely micro-scale businesses. Most of the traditional herbal medicine MSME players stated that they did not have a partnership. The results of the AHP analysis show that the traditional herbal medicine partnership model in Pamekasan can be formed through financial criteria with a weight of 0.498 and alternative capital criteria with a weight of 0.394. However, other criteria in the hierarchy also need to be considered in developing a partnership model for traditional herbal medicine SMEs in order to adapt to the conditions of traditional herbal medicine SMEs in Pamekasan.